Demographics and clinical characteristic of patients diagnosed with hen’s egg allergy (Annals of Medical Research, 2021)
Aim: To assess the demographics, clinical characteristics and natural course of patients diagnosed with hen’s egg allergy.Material and Methods: Patients who were diagnosed with hen’s egg allergy were included in this study. The patients’ medical records were analyzed to collect demographic and clinical data.Result: 88 patients diagnosed with hen’s egg allergy were included in the study. 46 (52.3%) of the patients were male, their median age was 33 months and their median follow-up period was 18 months. 44 (50%) of the patients had comorbid atopic disease. 49 (55.7%) of the children’s parents had a diagnosis of atopic disease, while 5 (5.7 %) had a diagnosis of food allergy. In terms of the patients’ clinical symptoms, 86 (97.7%) had cutaneous symptoms, 16 (18.2%) had gastrointestinal system symptoms, 13 (14.8%) had respiratory system symptoms. In the follow-up, 43 (48.9%) of the patients were found to develop tolerance. When the patients allergic to egg white and those allergic to egg yolk were compared in terms of clinical findings, atopic eczema exacerbation was found to be more frequent (p=0.012) in patients allergic to egg white; while urticaria (p=0.005) and cough (p=0.012) were found to be more frequent in patients allergic to egg yolk.Conclusion: In clinical presentations that develop as a result of egg allergy, the most frequent symptoms are dermatological, gastrointestinal system and respiratory system symptoms, respectively. However, while atopic eczema exacerbations are more frequent in patients allergic to egg white, symptoms related with respiratory tract are more common in patients allergic to egg yolk. Keywords: Allergy; Cow’s Milk; Persistence; Predictive Factors; Tolerance.
Keywords: Allergy; Cow’s Milk; Persistence; Predictive Factors; Tolerance.